Abscopal effect of focused ultrasound combined immunotherapy in animal solid tumor model: a systematic reviews and meta-analysis - Hu, Chao; Li, Hui; Deng, Tao; Liu, Zheng; Yang, Li; Peng, Li; Jiang, Ming Yan; Chen, Wen Zhi (Frontiers in Immunology, 2024)
IntroductionThe abscopal effect, a systemic anti-tumor response triggered by localized treatment, has gained attention but remains poorly understood. This study evaluates the efficacy and consistency of focused ultrasound (FUS) combined with immunotherapy in inducing the abscopal effect.MethodsA systematic review and meta-analysis were conducted on preclinical studies using solid tumor models. Data on tumor response, immune modulation, and survival outcomes were analyzed to assess the combination therapy's effectiveness.ResultsFUS combined with immunotherapy enhanced anti-tumor responses at local and distant sites, with evidence of immune activation and increased abscopal effect rates. However, heterogeneity across tumor models and protocols was observed.DiscussionThe findings provide a theoretical basis for FUS-immunotherapy combinations in cancer treatment, while emphasizing the need for standardized protocols and further research to elucidate underlying mechanisms.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023460710.